Pengendalian Kualitas Panen Berorientasi Good Agricultural Practices (GAP) Pada Kelapa Sawit (Elaeis guineensis Jacq.) - Trimo, Lucyana; Hidayat, Syarif (Universitas Galuh, 2024)
One of the important activities in oil palm cultivation is harvesting. This activity is very important because it is directly related to the yields quantity and quality, which will affect the farmer's income. In the Regulation of Agriculture Minister of the Republic of Indonesia No. 131/Permentan/OT.140/12/2013 concerning the Guidelines for Good Palm Oil Cultivation, states that farmers must implement Good Agriculture Practices (GAP). The aim of this research is to analyze the implmentation of GAP in oil palm harvesting activities by the Sukabumi II Farmers Group, the problems faced by farmers in implementing GAP, and find out the right solution. The research was carried out using a qualitative approach, and the research technique was a case study at the Sukabumi II Farmers Group in Lubuk Gaung Village, Sungai Sembilan Subdistrict, Dumai Municipality, Riau Province. Informants were selected purposively, namely: heads of farmer groups, Field Agricultural Extension, staff of related agencies, community leaders, and harvest workers. Data were analyzed descriptively and using the Causal Loop Diagram tool. The results of the research show that only around 25 percent of farmers in the Sukabumi II Farming Group carry out oil palm harvesting activities in accordance with the GAP. The problems faced by farmers in implementing GAP are: the narrow area of oil palm plantations, low knowledge about good harvest methods, have another more profitable jobs, and the merchant do not pay attention to the yields quality. The solution to the problems above are continuous coaching on the benefits of using the correct harvest method so as to increase the selling value of the harvest, and strengthening farmers' bargaining position through implementing a one-stop sales system.